Research on University Track & Field Web Courseâ??s Basic Attributes Columns - Lin, Weiliang (International Journal of Emerging Technologies in Learning (iJET), 2013)
The purpose of this paper is to perfect the effective construction of the web courseâ??s basic attributes modules, so as to help students get to know the personnel allocation and the resource integration efficiently and facilitate their learning online. The research methodology includes literature study, interview, system design method, software programming method, questionnaire survey and mathematical statistics and etc. Results: Firstly, the links between all the basic attributes modules are reasonable and fluent and it is also rich in content; secondly, the teaching staff and resource scale are reflected; thirdly, the course descriptions guide students to know the distribution of the course content better; fourthly, the courseâ??s self-evaluation and construction plan can objectively reflect its current situation and its development direction in the future. Conclusions: The content of the modules can effectively reflect the basic information of the faculty of the course, the whole teaching structure, teaching means and methods used in the course, the teaching conditions and effects and the construction schedules of online resources.